2009
DOI: 10.1590/s0074-02762009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Mansonella ozzardi in Brazil: prevalence of infection in riverine communities in the Purus region, in the state of Amazonas

Abstract: This study was undertaken to investigate the prevalence of Mansonella ozzardi infection and to estimate the parasitic infection rate (PIR) The filaria Mansonella ozzardi, one of the aetiological agents of mansonelliasis, is found on the American continent, as well as countries in the Caribbean. In South America, it has been reported in Panama, Colombia, Venezuela, Guyana, Suriname, Brazil, Argentina and Peru (Kozek et al. 1982). M. ozzardi is transmitted by Diptera insects of the families Ceratopogonidae in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 20 publications
7
36
0
12
Order By: Relevance
“…This filariasis was first reported in Brazil in the City of Manaus in the State of Amazonas 2 and people infected by M. ozzardi were later identified along the Solimoes, Purus and Negro Rivers 3 . These findings reinforce many studies that have warned that M. ozzardi was widely distributed in the State of Amazonas 4 , Brazil; however studies concerning this filariasis remain scarce [5][6][7] .…”
Section: Introductionsupporting
confidence: 85%
“…This filariasis was first reported in Brazil in the City of Manaus in the State of Amazonas 2 and people infected by M. ozzardi were later identified along the Solimoes, Purus and Negro Rivers 3 . These findings reinforce many studies that have warned that M. ozzardi was widely distributed in the State of Amazonas 4 , Brazil; however studies concerning this filariasis remain scarce [5][6][7] .…”
Section: Introductionsupporting
confidence: 85%
“…In addition, our results are in agreement with those of Batista et al 5 , Shelley 6 , and Medeiros et al 7 , who found no statistically significant difference in the prevalence rates between sexes. However, other epidemiological studies have reported a higher disparity between the prevalence rates in males and females 4,8 .…”
mentioning
confidence: 78%
“…There is a question of whether the diagnosis method used in this study was not sensitive enough to detect low rates of microfilaremia. However, many studies carried out in the Amazon use the same method and show prevalence of up to 60% of microfilaremia [7][8][9] . Another hypothesis may be that there are not enough individuals infected with a high enough parasite load to disseminate this endemic disease in areas not affected by the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Later, some researchers observed individuals infected with M. ozzardi alongside the Solimoes, Purus and Negro Rivers in the State of Amazonas [4][5][6] . Recent data have indicated that this parasite is still found with high prevalence rates in the Amazonian territory [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%